Digital TV and wireless multimedia communication : 16th International Forum, IFTC 2019, Shanghai, China, September 19-20, 2019, Revised selected papers /: 16th International Forum, IFTC 2019, Shanghai, China, September 19-20, 2019, Revised selected papers. (2020) - Unknown
No abstract available